The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7ra03281a
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of the orientation influenced He dissolution and diffusion behaviors on W surfaces

Abstract: The dissolution and diffusion behaviors of helium (He) for four low-Miller-index tungsten (W) surfaces [(110),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…For instance, Li et al. [ 31 ] introduced CDs with strong fluorescence into PNIPAM hydrogels via atom transfer radical polymerization. The CD/PNIPAM hybrid hydrogel showed a dramatic change in its fluorescence intensity at a lower critical solution temperature of 33 °C.…”
Section: Design and Construction Of Pgisdsmentioning
confidence: 99%
“…For instance, Li et al. [ 31 ] introduced CDs with strong fluorescence into PNIPAM hydrogels via atom transfer radical polymerization. The CD/PNIPAM hybrid hydrogel showed a dramatic change in its fluorescence intensity at a lower critical solution temperature of 33 °C.…”
Section: Design and Construction Of Pgisdsmentioning
confidence: 99%
“…12), which is consistent with the results reported in Refs. [48][49][50] using other simulation methods. Thus, the nanochannels not only shorten the diffusion distance of He atoms, but also promote the accumulation of He atoms at the nanochannel surfaces.…”
Section: Simulationmentioning
confidence: 99%
“…The average He-He binding energy in clusters is obtained as follows: Moreover, the He clusters (or a single He) induce the formation of W vacancies, interstitial atoms, and complexes in bulk W and on the W surface. [1,9,11] As the cluster size increases, the defects and vacancies become more obvious, as shown in Fig. 4.…”
Section: -2mentioning
confidence: 99%
“…Several other calculations have focused on the He dissolution and diffusion behavior on W surfaces. Pan et al [9] determined that He prefers to induce vacancies and interstitial W formations near the surfaces, which causes He accumulation on the surfaces. Hu et al [10] showed that trap mutation is an important reaction and found that this process significantly affects W surface morphology, structure, and He 𝑚 -V complex formation.…”
mentioning
confidence: 99%